2016
DOI: 10.1007/s00134-016-4638-3
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset moderate to severe acute respiratory distress syndrome is associated with shorter survival and higher mortality: a two-stage association study

Abstract: Purpose To evaluate the association between acute respiratory distress syndrome (ARDS) onset time and prognosis. Methods Patients with moderate to severe ARDS (N = 876) were randomly assigned into derivation (N = 520) and validation (N = 356) datasets. Both 28-day and 60-day survival times after ARDS onset were analyzed. A data-driven cutoff point between early- and late-onset ARDS was determined on the basis of mortality risk effects of onset times. We estimated the hazard ratio (HR) and odds ratio (OR) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…Zhang and colleagues studied patients with moderate to severe ARDS precipitated by a variety of ARDS risk factors, again dividing patients between early-and late-onset ARDS at 48 hours after admission. 78 In this study, late-onset ARDS was associated with a higher mortality than early-onset ARDS despite lower severity of illness scores at admission.…”
Section: Impact Of Clinical Variables On Ards Phenotypesmentioning
confidence: 54%
See 1 more Smart Citation
“…Zhang and colleagues studied patients with moderate to severe ARDS precipitated by a variety of ARDS risk factors, again dividing patients between early-and late-onset ARDS at 48 hours after admission. 78 In this study, late-onset ARDS was associated with a higher mortality than early-onset ARDS despite lower severity of illness scores at admission.…”
Section: Impact Of Clinical Variables On Ards Phenotypesmentioning
confidence: 54%
“…The Berlin Definition requires ARDS to develop within 1 week of the onset of the underlying precipitating illness 4 ; however, several researchers have identified significant heterogeneity based on the timing of onset of ARDS within that week. [75][76][77][78] Croce and colleagues first described early-and late-onset posttraumatic ARDS as distinct. 76 These authors defined early-onset ARDS as occurring within 48 hours after presentation and late-onset occurring beyond 48 hours after admission.…”
Section: Impact Of Clinical Variables On Ards Phenotypesmentioning
confidence: 99%
“…This nested case-control study was part of an ongoing Molecular Epidemiology Study of ARDS (MEARDS) at Harvard Medical School that was initiated in 2000. MEARDS has more than 4000 patients and includes both ARDS patients and at-risk controls who were critically ill patients admitted to the ICU of Massachusetts General Hospital (MGH; Boston, MA) or Beth Israel Deaconess Medical Center (BIDMC; Boston, MA) [ 13 , 14 ]. Commonly known ARDS risk factors and their definitions are listed in Additional file 1 : Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Both time of onset and duration of disease appear to hold prognostic value. Several studies have shown that ARDS onset >48 h after ICU admission is associated with higher mortality [15,16]. Not surprisingly, rapidly improving ARDS (ARDS that resolves within 1 day) has a better prognosis than persistent ARDS.…”
Section: Clinical Phenotyping For Prognostic Enrichmentmentioning
confidence: 99%